2007
DOI: 10.1053/j.gastro.2007.03.043
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Oral Erythromycin Decreased the Incidence of Parenteral Nutrition-Associated Cholestasis in Preterm Infants

Abstract: High-dose oral erythromycin can be considered as a rescue measure for VLBW infants who fail to establish adequate enteral nutrition and in whom anatomically obstructive pathologies of the gastrointestinal tract have been excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 69 publications
4
66
2
Order By: Relevance
“…None of our patients in the erythromycin group developed septicemia from antibiotic-resistant organisms. Infantile hypertrophic pyloric stenosis and life-threatening cardiac dysrhythmia have not been reported in previous clinical trials, 14,24,25 and we did not observe these in our patients. Our study demonstrated that erythromycin-treated infants had significantly fewer episodes of large residual gastric aspirates and were able to attain FEF more quickly, as noted in other.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…None of our patients in the erythromycin group developed septicemia from antibiotic-resistant organisms. Infantile hypertrophic pyloric stenosis and life-threatening cardiac dysrhythmia have not been reported in previous clinical trials, 14,24,25 and we did not observe these in our patients. Our study demonstrated that erythromycin-treated infants had significantly fewer episodes of large residual gastric aspirates and were able to attain FEF more quickly, as noted in other.…”
Section: Discussioncontrasting
confidence: 65%
“…14 Significantly fewer erythromycin-treated patients had abnormally raised serum alanine aminotransferase. 14 In our study, when we examined GGT elevation before and after treatment, the increase was found to be higher than in the placebo group. For that reason, it can be concluded that in the prevention of IFALD, erythromycin is more effective than is placebo.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…These infants often remain dependent on parenteral nutrition (PN) for survival and growth. However, prolonged PN has been associated with serious complications, including nutritional deficiencies, risks secondary to central venous catheters and PN-associated cholestasis (PNAC) [1,2]. Neonatal PNAC is characterised by intrahepatic cholestasis and liver fibrosis and in severe cases can result in liver failure, with corresponding derangement in liver function, including raised plasma-conjugated bilirubin (CBil) and alanine aminotransferase (ALT) [3].…”
Section: Introductionmentioning
confidence: 99%
“…With regards to safety of erythromycin, we found no diarrhea, arrhythmia, or hypertrophic pyloric stenosis in the treatment group, similar to other studies. 16,19,20 Long-term erythromycin can change the normal intestinal flora, with high-dose or therapeutic doses leading to diarrhea and sepsis. 21,22 However, Ng found no intestinal microorganism changes after the use of erythromycin for 10 days and 4 weeks.…”
Section: Discussionmentioning
confidence: 99%